Counterimages of TV Fiction: Towards an Apophatic Aesthetic of Contemporary Seriality in the Digital Age - Pintor Iranzo, Ivan (Funes. Journal of narratives and social sciences, 2024)
The conclusion of Twin Peaks’ third season (also known as Twin Peaks: The Return) marks a pivotal moment for investigating contemporary television narratives through a negative or apophatic aesthetic lens, inspired by theological concepts of denial and mysticism. This study explores how modern digital serial storytelling embodies themes of negativity, drawing on a hermeneutic methodology informed by iconographic analysis and post-Heideggerian philosophy, particularly referencing Giorgio Agamben. By integrating insights from diverse artistic disciplines such as plastic arts, dance, and religious mysticism, the analysis deepens our understanding of narrative constructions in series like Twin Peaks: The Return, and True Detective. This interdisciplinary approach illuminates television’s engagement with apophatic aesthetics and invites critical reflection on the intersection of digital seriality, theological discourse, and artistic expression within contemporary media culture.